Sahityayetihaas Lekhan Ki Parampara Kaal Vibhajan Tatha Naamkaran: Exploring the Evolution of Literary History and Naming Conventions in Sahityayetihaas Lekhan Tradition (Journal of Advances and Scholarly Researches in Allied Education, 2013)
lkfgR;sfrgkl vFkkZr~ lkfgR; dkbfrgkl] vr% lkfgR;sfrgkl ys[ku dk rkRi;Z lkfgR; dk bfrgkl&ys[ku gh gSAKku&foKku dh cgqfo/k fo/kkvksa esa lokZf/kd foLr`r] O;kid vkSj fojkV fo/kklkfgR; gh gSA lkfgR; vFkkZr~ vfHkO;fDr dk og iVy ftl ij ekuo dk lEiw.kZ thou:ikf;r gksrk gSA ,sls lkfgR; dk bfrgkl&ys[ku ,d nq’dj dk;Z gS] blfy, foLr`rv/;;u] iz[kj izfrHkk] lw{e rFkk xgjh le> rFkk izk´ty vfHkO;fDr dh vko”;drkgksrh gSA lkfgR;sfrgkl ds ys[kd ds fy, ;g vko”;d gS fd og lkfgR; dh laosnuk]dYiuk”khyrk] dkseyrk] jkxkRedrk] thou&izfrc)rk ds lkFk bfrgkl dh;FkkFkZrk] rkfdZdrk] ?kVukc)rk] vUos’k.k dh {kerk dk larqfyr] lkFkZd] lEizHkkohlarqyu LFkkfir dj ldsA